Development And Quality Evaluation of Microencapsulated Banana Pseudostem Juice Powder - SARANYA S; Dr. Sudheer K.P (Guide) (Tavanur 2017 Kelappaji College of Agricultural Engineering and Technology)
Development And Quality Evaluation of Micro encapsulated Banana Pseudostem Juice Powder
Development And Quality Evaluation of Micro encapsulated Banana Pseudostem Juice Powder